2019
DOI: 10.1177/1473225419869568
|View full text |Cite
|
Sign up to set email alerts
|

Youth Justice in the Digital Age: A Case Study of Practitioners’ Perspectives on the Challenges and Opportunities of Social Technology in Their Techno-Habitat in the United Kingdom

Abstract: This article draws on original, empirical research that focused on the use of an experimental mobile application developed by the authors and used in the domain of youth justice in England. Against a backdrop of the theory of the paradox of technology with ideas of the networked self and child rights, the article explores the use of social technology with vulnerable/marginalised young people. Given the dearth in knowledge and understanding, in this area of social technology and young people in conflict with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Some men leaving prisons are given a phone on their release (Reisford and Rikard 2018). A recent United Kingdom study of the integration of an app within youth offending services has proved effective for improving relationships between caseworkers and youths, empowering youths through access to personalized information, and helping them comply with court conditions through online schedules and appointments (Barn and Barn 2019). The incorporation of digital technology has a crucial role in young people's rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some men leaving prisons are given a phone on their release (Reisford and Rikard 2018). A recent United Kingdom study of the integration of an app within youth offending services has proved effective for improving relationships between caseworkers and youths, empowering youths through access to personalized information, and helping them comply with court conditions through online schedules and appointments (Barn and Barn 2019). The incorporation of digital technology has a crucial role in young people's rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Practitioners' inabilities to understand phones as anything but a negative force inhibiting them from identifying how a phone could be a device for preventing offending. Like JJS practitioners from the United Kingdom, participants did not routinely use digital spaces with their young people (Barn and Barn 2019). Practitioners found it difficult to understand why phones were so important for girls, which led to them minimizing girls' experiences causing numerous misunderstandings and tension between girls and keyworkers.…”
Section: Why Practitioners Favor Digital Bansmentioning
confidence: 99%
“…Indeed, panel members have expressed concerns about the virtual platform, telling HMIP (2020a) that they ‘couldn’t really get a sense of the child and too much was lost in not being able to see the non-verbal communication and dynamics between children and their parents and carers’ (p. 20). Informal conversations with YOT staff showed that some children benefitted from contacts facilitated through video calls, seeming to prefer to ‘meeting’ workers virtually resulting in better engagement (a gain ), possibly ushering in the new world of digital working as envisioned by Barn and Barn (2019) . This was echoed in the inspection, which found that both children and their families reported virtual contact as ‘less intense and “scary”’ ( HMIP, 2020a : 22).…”
Section: The Pains and Gains Of Covid-19 In The Communitymentioning
confidence: 99%
“…phones, tablets). Barn and Barn (2019) described the development of Mobile Apps in Youth Offending Teams (MAYOT) (Table 3), in the youth justice context in England. The purpose of the MAYOT app is to help reduce re-offending behaviours in young offenders, by supporting them with their compliance conditions and requirements around key goals and outcomes.…”
Section: Mobile Appsmentioning
confidence: 99%
“…To enhance the app's utility, case workers could use the software on their desktop computers and send information that clients could access on their mobile phones. Barn and Barn's (2019) research focuses on the experiences and views of practitioners, rather than the experiences of clients (e.g. young people), which might be a limitation.…”
Section: Mobile Appsmentioning
confidence: 99%